2013
DOI: 10.1029/2012gl054280
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of bedload transport over steep slopes: Separation of time scales and collective motion

Abstract: [1] Steep slope streams show large fluctuations of sediment discharge across several time scales. These fluctuations may be inherent to the internal dynamics of the sediment transport process. A probabilistic framework thus seems appropriate to analyze such a process. In this paper, we present an experimental study of bedload transport over a steep slope flume for small to moderate Shields numbers. The sampling technique allows the acquisition of highresolution time series of the solid discharge. The resolved … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 18 publications
(45 reference statements)
4
83
0
Order By: Relevance
“…These data come from earlier experimental campaigns conducted on steep slopes, thus in the supercritical regime (Böhm et al 2004;Ancey et al 2008;Heyman et al 2013), but the theory applies to subcritical regimes as well. Only essential details of methodology, data processing and results are presented here.…”
Section: Applicationsmentioning
confidence: 95%
“…These data come from earlier experimental campaigns conducted on steep slopes, thus in the supercritical regime (Böhm et al 2004;Ancey et al 2008;Heyman et al 2013), but the theory applies to subcritical regimes as well. Only essential details of methodology, data processing and results are presented here.…”
Section: Applicationsmentioning
confidence: 95%
“…Although the movement of grains in natural channels has advantages over simplified flume experiments, unless those grains have radio-tags or embedded accelerometers (see Section 2.2) it is very difficult to know the exact travel distances, rest times, travel velocities, and shear stresses at entrainment or disentrainment. Laboratory experiments using videos or impact plates have allowed for such details to be accurately measured for relatively simple bed conditions (e.g., Heyman et al, 2013). For example, experimental observations have shown that the number of moving particles increases faster with excess shear stress than particle velocities or step lengths and suggests that bedload fluxes are largely driven by particle activity (e.g., Lajeunesse et al, 2010;Roseberry et al, 2012;Furbish and Schmeeckle, 2013).…”
Section: Grain Scale Transport Mechanicsmentioning
confidence: 98%
“…While suspended sediment represents the largest fraction of mass exiting the landscape (Milliman and Syvitski, 1992;Willenbring et al, 2013), it is coarse bed load transport that sets the limiting rate of landscape incision through its control on bedrock erosion and channel geometry in gravel rivers (Sklar and Dietrich, 2004;Snyder et al, 2003;Parker et al, 2007). The rate of bed load transport is known to vary both spatially and temporally due to turbulence and granular phenomena such as clustering, bed forms, bed compaction, grain protrusion/hiding, and collective motion (Gomez, 1991;Kirchner et al, 1990;Schmeeckle et al, 2001;Strom et al, 2004;Ancey et al, 2008;Zimmermann et al, 2010;Marquis and Roy, 2012;Heyman et al, 2013), which makes predictions difficult (Recking et al, 2012) and point measurements highly variable (e.g., Gray et al, 2010). Bed load is especially difficult to predict near the threshold of motion (Recking et al, 2012), where transport is highly intermittent, often resulting in partial bed load transport, in which only a fraction of the bed is mobilized during a transporting event (Wilcock and McArdell, 1997).…”
Section: Introductionmentioning
confidence: 99%